Comparison of early and late outcomes of TAVI alone compared to TAVI plus PCI in aortic stenosis patients with and without coronary artery disease. Issue 4 (31st October 2013) - Abramowitz, Yigal; Banai, Shmuel; Katz, Guy; Steinvil, Arie; Arbel, Yaron; Havakuk, Ofer; Halkin, Amir; Ben‐Gal, Yanai; Keren, Gad; Finkelstein, Ariel
<x xml:space="preserve">Abstract</x> Objectives To assess the safety and effectiveness of performing percutaneous coronary intervention (PCI) before transcatheter aortic valve implantation (TAVI). Background The presence of coronary artery disease (CAD) negatively impact procedural outcomes and long‐term survival after (TAVI). The management of obstructive CAD before TAVI is not yet well established. Methods Patients with severe symptomatic aortic stenosis (AS) (n = 249) that underwent TAVI were divided into two groups: patients with CAD (subdivided to patients treated with TAVI alone and to patients that underwent PCI before TAVI) and patients with isolated AS. Procedural endpoints, device success and adverse events were considered according to the Valve Academic Research Consortium (VARC) definitions. Results Of a cohort of 249 consecutive patients with mean age of 83.2 ± 5.5 years, 83 patients with AS + CAD were treated with TAVI alone, 61 patients with AS + CAD underwent PCI before TAVI and 105 patients underwent TAVI for isolated AS. The mean duration of follow‐up was 17 months (range: 6–36 months). Despite a significantly higher logistic EuroScore of the AS+CAD group compared to the AS alone group (30.1 vs. 21.1 P < 0. 001), the overall VARC‐adjudicated endpoints did not differ between the groups. All‐cause mortality at 30‐days was 1.6% for patients with AS+CAD treated with PCI compared to 2.9% for patients with AS alone (P = 1). Conclusions Performing PCI before TAVI in high‐risk elderly patients with significant CAD and severe AS is feasible and safe. This combined treatment approach did not increase the periprocedural risk for complications or the all‐cause mortality. © 2013 Wiley Periodicals, Inc.